A systematic review of interventions to improve postpartum retention of women in PMTCT and ART care - Geldsetzer, Pascal; Bärnighausen, Till (Journal of the International AIDS Society, 2016)
Introduction : The World Health Organization recommends lifelong antiretroviral therapy (ART) for all pregnant and breastfeeding women living with HIV. Effective transitioning from maternal and child health to ART services, and long-term retention in ART care postpartum is crucial to the successful implementation of lifelong ART for pregnant women. This systematic review aims to determine which interventions improve (1) retention within prevention of mother-to-child HIV transmission (PMTCT) programmes after birth, (2) transitioning from PMTCT to general ART programmes in the postpartum period, and (3) retention of postpartum women in general ART programmes. Methods : We searched Medline, Embase, ISI Web of Knowledge, the regional World Health Organization databases and conference abstracts for data published between 2002 and 2015. The quality of all included studies was assessed using the GRADE criteria. Results and Discussion : After screening 8324 records, we identified ten studies for inclusion in this review, all of which were from sub-Saharan Africa except for one from the United Kingdom. Two randomized trials found that phone calls and/or text messages improved early (six to ten weeks) postpartum retention in PMTCT. One cluster-randomized trial and three cohort studies found an inconsistent impact of different levels of integration between antenatal care/PMTCT and ART care on postpartum retention. The inconsistent results of the four identified studies on care integration are likely due to low study quality, and heterogeneity in intervention design and outcome measures. Several randomized trials on postpartum retention in HIV care are currently under way. Conclusions : Overall, the evidence base for interventions to improve postpartum retention in HIV care is weak. Nevertheless, there is some evidence that phone-based interventions can improve retention in PMTCT in the first one to three months postpartum. Keywords: PMTCT; retention; Option B+; postpartum; HIV; antiretroviral therapy; loss to follow-up.
Gesehen am 30.05.2017